Exploring identity in coaching – insights into coaches’ understanding and approach - Lazarus, Alex (Frontiers in Psychology, 2025)
Responding to a growing focus on identity within academia and the shifting socio-economic landscape, this study investigates the role of identity in executive coaching. Given identity’s complexity, its impact on human thriving, and its critical role in HRD, this research examines how coaches perceive, engage with, and address identity-related issues. Specifically, it explores how coaches navigate these issues without a standard theoretical framework, aiming to fill notable gaps in the literature on identity coaching and its methods. A qualitative, experiential approach was adopted, with purposive sampling used to select 14 experienced executive coaches from the United Kingdom, United States, and New Zealand. Data collection involved semi-structured interviews conducted over three weeks, followed by inductive thematic analysis, allowing key themes to emerge organically from participants’ insights. The analysis revealed five primary themes shaping coaches’ work with identity: the importance of a whole-person approach, identity’s central role in coaching, the coach as an instrument, methods and tools employed, and implications for coach education. While most coaches favoured an “inside-out” approach, emphasising the coachee’s self-concept and identity dynamics, they noted challenges in defining identity consistently, often shaped by their own experiences. Furthermore, while viewing this level of coaching as transformational, many also highlighted potential risks inherent in deep identity work, including unintended impacts on coachees’ personal lives. Ultimately, the findings underscore significant gaps in identity-related coaching frameworks and training, highlighting the need for more systematic approaches to addressing identity issues. To meet these challenges, the study recommends developing comprehensive resources and training to equip coaches for effective identity coaching practices.